Norwegian Nurses’ Reflections Upon Experiences of Ethical Challenges in Older People Care: A Qualitative Thematic Analysis - Linda Rykkje PhD, RN, MNSc (SAGE Publishing, 2021)
Introduction Internationally, aging populations have increased needs for health care services, and often specialized care is required. However, services for older people tend to be underfunded, resulting in lack of qualified staff and poor quality care. Resource shortages lead to ethical challenges and insufficient nursing care. Therefore, quality in daily care for older people also depends upon the nurses’ ability to make complex, ethical decisions in their practice. Objectives To explore ethical challenges experienced by nurses caring for older people in clinical practice, and to provide examples of management for the challenges. Methods The data collected were written reflection notes by Norwegian continuous education students in advanced gerontology. Forty two of 83 notes were included and a thematic analysis in six steps was utilized. Findings There are three main themes: (1) meeting vulnerability, discomfort, and suffering, (2) collaboration with relatives, and (3) struggling to perform professional care. Conclusion Nurses strive to “do what is in the patients’ best interest”, and this is fostered through collaboration, professionalism, care, and presence. Nurses’ ethical competencies may develop when reflecting upon their own care performance. Building ethical competencies should be a priority in both nursing education and clinical practice. However, to improve care quality, nurses also need professional knowledge about older people care and ethical awareness should be supported by the workplace.